Optimal location of facts for ATC enhancement by using sensitivity analysis - Al Shaikh Salem, Raimon Omar (2013)
According to the changes in power structure (deregulation), competitive markets became in urgent need to have ability to satisfy the rise of energy demands. However, it is limited into the existing transmission grids. In order to extend the grid, it accompanies with problems as huge cost and large required time. Therefore, markets pay attention to have optimal utility of the current transmission system. That comes through the Available Transfer Capability (ATC) which is computed using Repeated Power Flow (RPF) technique. In order to have improvement in ATC, Flexible AC Transmission System (FACTS) devices are used to control power flow and improve the voltage and power profiles in the transmission system. In this project, two types of controllers are used Static Synchronous Compensator (STATCOM) and Unified Power Flow Controller (UPFC). The insertion of the controller in the power system comes through determining the specific location in the transmission system; the proposed method is called Sensitivity Analysis. This project is applied on 5, 14 and 24 IEEE bus power systems in Power system Analysis Toolbox (PSAT) software. The proposed method has yielded excellent results in both reducing loss and improvement of ATC in simulated power systems.